Ready‐to‐Use Stocks of Agrobacterium tumefaciens Can Simplify Process Development for the Production of Recombinant Proteins by Transient Expression in Plants. Issue 10 (18th July 2019) - Spiegel, Holger; Boes, Alexander; Perales Morales, Camil; Rademacher, Thomas; Buyel, Johannes F.
Abstract : Large‐scale automated transient protein expression in plants requires the synchronization of cultivation and bacterial fermentation, especially if more than one bacterial strain. Therefore, a ready‐to‐use approach that decouples bacterial fermentation and infiltration is developed. It is found that bacterial cultures can easily be reconstituted in infiltration medium at a user‐defined time, optical density, and quantity. This allows the process flow to be staggered, avoiding bottlenecks in process capacity and labor. Using the red fluorescent protein, DsRed, as a model product, the ready‐to‐use preparations achieved the same yields in infiltrated plant biomass as Agrobacterium tumefaciens derived from regular fermentations. It is possible to store the ready‐to‐use stocks at –20 °C and –80 °C for more than two months without loss of activity. Using a consolidated cost model for the current fermentation process, it is found that the ready‐to‐use strategy can reduce operational costs by 20–95% and investment costs by up to 75%, which would otherwise offset the economic advantages of plants over mammalian expression systems during upstream production. Furthermore, the staggered cultivation of plants and bacteria reduces the likelihood of batch failure and thus increases the robustness and flexibility of transient expression for the production of recombinant proteins in plants. Abstract : Agrobacterium tumefaciens facilitates rapid, transient expression of recombinant proteins in plants. Here, a new method to store the bacteria in a ready‐to‐use frozen form is developed. This method allows flexible use of fermentation capacity, reduces the risk of batch failure and can save costs by reducing the number of fermentations required for a production campaign.